Microstructural analysis on the testicular cyst of the wolf spider by 3D volume rendering. Issue 1 (20th January 2014) - Kim, Hoon; Kim, Jae‐Kyung; Moon, Myung‐Jin
Abstract Spermatogenesis has long been a major research area in understanding the development of living organisms. In vertebrates, sperm is produced along the wall of the seminiferous tubules, leaving spermatogonia in the outermost layer, which undergo cell division and differentiation. However, sperm in many invertebrates is developed in a testicular cyst, which contains germ cells at the same developmental stages. On the contrary, in spiders, it is very difficult to count the exact number of cells in a cyst, since each spermatid gets transformed to a round sperm ball within the cyst through the flagellar coiling process. Therefore, in this study, we applied a 3D rendering technique to analyze the exact number of germ cells per cyst in spiders. For image processing and reconstruction, serial section images were scanned and reconstructed into 3D images. Upon successful 3‐dimensional reconstruction of testicular cysts, the exact number of germ cells produced from a single cyst appeared to be 64, 26 which indicates that a spider spermatogonium undergoes 6 cell divisions to produce spermatozoa.